Óbidos, literary village: innovation in the creative industries? - Centeno, Maria João (2016)
The village of Óbidos was recognized in 2015 as a creative city in the area of literature, becoming a member of the UNESCO Creative Cities Network. The attribution of the title depends on the fulfillment of a number of criteria the regions have to integrate. In addition to Óbidos, UNESCO attributed the same title in the same year to other European cities, including Barcelona, Nottingham, Ljubljana, Tartu and Lviv. This article intends to co nduct a case study to the cultural and artistic offer, as well as the cultural and literary legacy that different cities provide to be able to inquire the innovation of the proposals. The study aims to assess how much Óbidos, compared to other cities with the same title, is creative. Knowing that the concept of creative city (Landry and Bianchini, 1995) results from the emergence of new technologies and a new type of economy based on creativity and innovation and that creativity implies removing economic or social value of the creative work or talent, the study aims to determine to what extent the processes generated gave rise to new ideas (creativity) and what processes led to its implementation (innovation). Being innovation in the creative industries asso ciated with product, process, positioning, paradigmatic and social innovation (Storsul and Krumsvik, 2013), it is concluded that, in Óbidos, the entrepreneurship initiatives are more focused on tourists who occasionally visit the village and the business o pportunities that are generated there. New innovative and creative spaces were created, promoting literature and adding value and quality to urban space. This urban intervention resulted in the attraction of individuals who streamlined new habits of being and acting in the village